2015
DOI: 10.1097/acm.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Mental Health and Well-Being of Sexual Minority and Heterosexual First-Year Medical Students

Abstract: Purpose Research is lacking on psychological distress and disorder among sexual minority medical students (students who identify as non-heterosexual). If left unaddressed, distress may result in academic and professional difficulties and undermine workforce diversity goals. The authors compared depression, anxiety, and self-rated health among sexual minority and heterosexual medical students. Method This study included 4,673 first-year students with self-reported sexual orientation data in the fall 2010 base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 58 publications
6
74
2
1
Order By: Relevance
“…As well, the study targeted only one medical school, and a broader study is required to be able to assess Canadian medical schools overall. Finally and similar to literature, LGBT students represented a high proportion among respondents (35.9%), likely higher than the true proportion among medical students estimated at 5.0% [1]. The higher response rate noted in our study can be explained by LGBT students showing a higher interest in healthcare issues related to their own community [35].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As well, the study targeted only one medical school, and a broader study is required to be able to assess Canadian medical schools overall. Finally and similar to literature, LGBT students represented a high proportion among respondents (35.9%), likely higher than the true proportion among medical students estimated at 5.0% [1]. The higher response rate noted in our study can be explained by LGBT students showing a higher interest in healthcare issues related to their own community [35].…”
Section: Discussionsupporting
confidence: 84%
“…A recent study found LGB medical students to be more likely to report social stressors (including harassment) as well as social isolation [1], placing them at greater risk of depression and anxiety. In our study, LGBT students had higher odds for witnessing overt discrimination and for describing a less inclusive environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual minority (SM) medical students are more likely than non-SM students to report stress, isolation, verbal insults, and harassment or threats 5 and they are approximately twice as likely to experience depression and related mental health comorbidities. 5,6 Almost one-fifth of lesbian-identified physicians report sexual orientation harassment during residency, and two-fifths report ever experiencing such harassment in a medical setting.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Almost one-fifth of lesbian-identified physicians report sexual orientation harassment during residency, and two-fifths report ever experiencing such harassment in a medical setting. 7 Two-thirds of SGM physicians have heard disparaging remarks about SGM at work; one-third have witnessed discriminatory care of an SGM patient; approximately one-quarter have witnessed discrimination against an SGM employee; and approximately one-fifth report experiencing social ostracism because of their SGM identity.…”
Section: Introductionmentioning
confidence: 99%